Performance Measurement Based on the Green Manufacturing Concept with Organization for Economic Co-operation and Development Indicators - Prastian, Favian; Pudji, Endang (Newinera Publisher, 2024)
When a country builds factories and industries, it helps the country grow and become better. It can create more jobs and make things run faster. But sometimes, these factories can make the water and water dirty. Therefore, it is necessary to measure company performance based on the concept of green manufacturing. The indicators used in measuring company performance are green manufacturing indicators based on the Organization for Economic Co-operation and Development (OECD). In the research results, out of 18 indicators, 5 indicators were found to be unfulfilled, these indicators are the intensity of water pollution at the process stage, energy consumption in using products at the output stage, and greenhouse gas emissions in using products at the output stages. With 13 indicators that are in line with the concept of green manufacturing, the performance of PT. XYZ related to the concept of green manufacturing is included in the Advance category.